Astyanax guaricana(Ostariophysi: Characidae), a new species from the rio Cubatão drainage, Paraná State, Southern Brazil - Oliveira,Carlos A. M. (2013)
In this paper we describe a new species of Astyanax collected in the Atlantic Rainforest, in tributaries to the rio Cubatão, coastal basin of the Paraná State, Brazil. The new species presents a combination of characters that allows its allocation in the A. scabripinnis species complex and differs from congeners by the possession of 18 to 22 branched anal-fin rays; 40 to 43 perforated scales in lateral line; dentary teeth decreasing abruptly in size from the fifth tooth; 15 to 17 circumpeduncular series of scales and two vertical humeral spots